COVID-19 e a subjetividade no contexto das mudanças ambientais - de Paula Peres, Silvia Miguel; Heuminski de Avila, Ana Maria; da Cal Seixas, Sônia Regina (Espacio Abierto, 2021)
The article presents a reflection regarding the linearity of causal relationships that involve environmental changes and their impact on (human) subjectivity. The environmental changes are here identified as transformations of natural, climatic, and socio-cultural systems resulting from contemporary lifestyle, and the impacts as the dimension of feelings and sensations related to these changes. The authors carried out conceptual theoretical debates to situate the covid-19 pandemic as a disaster associated with the contemporary way of life present in the urbanization process of cities. In moments of intense environmental change, such as the dystopian scenario represented by the advent of COVID-19, the more daily life is reconstituted at the confluence between the local and the global, the more individuals suffer, develop fears, and are challenged to develop survival strategies. Thus, subjectivity is more than a consequence of the pandemic disaster, it is conceptualized as a transformative potential – a dynamic continuum – expanding its scope as a perspective for action facing disaster. Future uncertainties may trigger processes to constitute new realities through political opportunities that favor creativity, seen as a coping strategy. The resumption of adaptive paths in the face of ongoing transformations may be possible, whether the “poetics of existence” finds its emergency and performance space.